Incontinentia pigmenti: A propósito de un caso. - Carlos, Tori Tori (2013)
Incontinentia Pigmenti is a rare X-linked multisystem neuroectodermic disorder with signs and symptoms related mainly to the dermatologic, dental, ocular and central nervous systems, and characterized by death in the majority of male embryos. Affected children do not appear sick, in spite of the skin eruption, the peripheral leucocytosis and marked eosinophilia. Most of the cases are reported in caucasians, although there are description in black children, orientals, north central and south american Indians, and in our mestizos. The name of Incontinentia Pigmenti describes the incontinence of the melanin pigment from the basal layer of the epidemermis into the superficial dermis.